Peningkatkan Daya Saing Smp Melalui Penguasaan It Dan Ketrampilan Pembuatan Modul Penampil Informasi Led Matrix. - Erfan Achmad Dahlan (Journal of Innovation and Applied Technology, 2018)
One of the major issues often faced by private schools is the shortage of learners The minimum number of applicants seems to be a "chronic illness" suffered each before the new school year. Private schools should rise from this adversity by trying to stand on their own feet. The improvement of the quality of education services is an absolute requirement that must be met. Therefore, increasing competitiveness among other schools is a necessity.IbM Junior High School   activity is intended to improve the competitiveness of Muhammadiyah 4 and 6 Junior High School  in Malang through exposing the potential of schools in the community through the weblog of teachers and schools, as well as improving the skills of teachers and students through mastering the assembly of Running Text LED MATRIX module as a medium of information delivery.